The roles, resources and competencies of employee lay judges: A cross-national study of Germany, France and Great Britain - Pete Burgess; Susan Corby; Armin Höland; Hélène Michel; Laurent Willemez; Christina Buchwald; Elisabeth Krausbeck (Hans-Böckler-Stiftung, 2017)
This research project analysed and compared the roles, resources and competencies of lay judges in Germany, France and Great Britain, where lay judges take up their role through nationally distinctive routes: nomination essentially by the social partners in Germany, self-nomination in Great Britain and election in France. The primary research consisted of qualitative data collected through interviews, set against contextual information on national institutional arrangements, industrial relations, and court procedures.
urn:nbn:de:101:1-201711153217
Keywords: 330